EFFECT OF CHANGE MANAGEMENT DRIVER ON PERFORMANCE OF THE TOURISM STATE OWNED CORPORATIONS IN KENYA - Muthoka, Miriam; Oloko, Dr.Margaret; Obonyo, Dr. Levi (European Journal of Business and Strategic Management, 2017)
Purpose: This study sought to provide an opportunity to test effect of management change driver on performance of the Tourism state owned corporations in Kenya. Methodology:The study employed descriptive and cross-sectional research designs. The target population comprised all the Tourism state owned corporations in Kenya with the management of these firms being the respondents. A census study was carried out due to small nature of the target population. Data collection involved the use of questionnaires which attracted both quantitative and qualitative responses. The questionnaires were administered through drop and pick method. The respondents were all the Chairmen, CEO, managers and assistant managers of all Tourism state corporations in Kenya. The quantitative data was analyzed using regression analysis. ANOVA test was carried out to test the significance of the model. Results:The findings of the study indicated that change management driveraffects performance of most tourism state corporations in Kenya. The study further found out that positive organization culture, change execution and consistency in change vision affected performance of the Tourism state corporations in Kenya to a great extent respectively. Having consistency in change vision, consensus in decision making and practicing positive organization culture were positively and significantly related to performance of the Tourism state corporations in Kenya. The findings of the study further indicated that change management driverwas positively correlated to organization performance and itexplains 17% of the changes in performance of the organizations. The regression model results indicated that the coefficient for change management capability was significant at 5% level of significance which indicated that change management capabilityhas a significant effect on performance in the Tourism state corporations in Kenya. Policy recommendation: Tourism state corporations in Kenya should embrace and practice positive organization culture, change execution and consistency in change vision since they influences performance positively.